Cytomegalovirus colitis in patients with acquired immunodeficiency syndrome. - DeRodriguez, C V (1994)
The spectrum of presentation of complications in patients with human immunodeficiency virus (HIV) disease is changing, in line with their improved survival. Infection of the colon with cytomegalovirus (CMV) is now more commonly encountered in clinical practice. We have reviewed the medical records of eleven patients with clinical and pathological evidence of CMV colitis. The clinical presentation, endoscopic and histological findings, and simultaneous infection of other organs with CMV are discussed. Diarrhoea in association with abdominal pain is the most frequent symptom complex in these patients and should raise the clinical index of suspicion for CMV colitis.